2011
DOI: 10.1073/pnas.1100125108
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical characterization of two binding sites for nucleation-promoting factor WASp-VCA on Arp2/3 complex

Abstract: Actin-related protein (Arp) 2/3 complex mediates the formation of actin filament branches during endocytosis and at the leading edge of motile cells. The pathway of branch formation is ambiguous owing to uncertainty regarding the stoichiometry and location of VCA binding sites on Arp2/3 complex. Isothermal titration calorimetry showed that the CA motif from the C terminus of fission yeast WASP (Wsp1p) bound to fission yeast and bovine Arp2/3 complex with a stoichiometry of 2 to 1 and very different affinities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
170
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 131 publications
(196 citation statements)
references
References 45 publications
21
170
4
1
Order By: Relevance
“…These techniques allowed us to directly measure key features of Arp2/3 complexmediated branch formation, including Arp2/3 binding and dissociation rates, branch formation efficiency, and activation time, and to determine how these parameters are affected by VCA. Earlier studies observed actin only (4, 5), or used indirect bulk methods based on fluorescence enhancement of pyrene-actin and/or pyrene-Arp2/3 complex (15,17,18). Our activation timedelay results are roughly consistent (within ∼10-fold; SI Materials and Methods) with those derived from kinetic modeling based on earlier observations.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…These techniques allowed us to directly measure key features of Arp2/3 complexmediated branch formation, including Arp2/3 binding and dissociation rates, branch formation efficiency, and activation time, and to determine how these parameters are affected by VCA. Earlier studies observed actin only (4, 5), or used indirect bulk methods based on fluorescence enhancement of pyrene-actin and/or pyrene-Arp2/3 complex (15,17,18). Our activation timedelay results are roughly consistent (within ∼10-fold; SI Materials and Methods) with those derived from kinetic modeling based on earlier observations.…”
Section: Discussionsupporting
confidence: 79%
“…Our activation timedelay results are roughly consistent (within ∼10-fold; SI Materials and Methods) with those derived from kinetic modeling based on earlier observations. However, our observations reveal that binding and most dissociation of Arp2/3 complex from filaments is ∼100 and ∼1,000-fold faster than inferred previously (15). Conversely, branch formation is extremely inefficient (0.5-1.5%), in contrast to the ∼100% efficiency that would be implied if dissociation were slow.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations